Changing practices in evaluating teaching: a practical guide to improved faculty performance and promotion/tenure decisions - Seldin, Peter (Jossey-Bass, 2007)
Over recent decades, the evaluation of teaching has undergone dramatic change. In accessible language and supportive detail, Changing Practices in Evaluating Teaching provides not only a cogent overview of these changes but also reflects on current developments to present several useful strategies for implementing new tools and methods in the evaluation of teaching. The authors are all prominent educators who have performed seminal work in the improvement of teaching evaluation. Written for university and college administrators as well as faculty, this book is a complete guidebook that supplies a wealth of case studies, examples, tables, Web sites, and exhibits that further enhance its utility. It explains how to Gain genuine faculty and administrative support Avoid common weaknesses in teaching evaluation by students, peers, and self Evaluate teaching by examining student learning Successfully combine disparate sources of data Establish a climate conducive to evaluation How to structure and use classroom visits, rating forms, electronic classroom assessment, and teaching portfolios Changing Practices in Evaluating Teaching makes evident the compelling reasons why colleges and universities must institute fair teaching evaluation systems, and explains how to do so. With a notable focus on improving student learning, this book offers readers the kind of research-based and ready-to-use information required to foster truly effective and equitable teaching evaluation at their institutions.